2020
DOI: 10.5194/wes-2020-54
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Laminar-turbulent transition characteristics of a 3-D wind turbine rotor blade based on experiments and computations

Abstract: Abstract. Laminar-turbulent transition behaviour of a wind turbine blade section is investigated in this study by means of field experiments and 3-D computational fluid dynamics (CFD) rotor simulations. The power spectral density (PSD) integrals of the pressure fluctuations obtained from the high frequency microphones mounted on a blade section are analyzed to detect laminar-turbulent transition locations from the experiments. The atmospheric boundary layer (ABL) velocities and the turbulence intensities (T.I.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In their work, Ozçakmak et al 26,39 performed the analysis of field transition measurements for the tip section, focusing on the boundary layer transition laminar to turbulent. They showed that the turbulent inflow and surface roughness were the main contributors in the boundary layer transition.…”
Section: Field Measurements Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In their work, Ozçakmak et al 26,39 performed the analysis of field transition measurements for the tip section, focusing on the boundary layer transition laminar to turbulent. They showed that the turbulent inflow and surface roughness were the main contributors in the boundary layer transition.…”
Section: Field Measurements Analysismentioning
confidence: 99%
“…The tangential force measurement, F t , is also impacting the lift force F L through the projection of the rotor forces onto the local aerofoil reference frame (see Figure 5). The relationship is made through the inflow angle , and looking at Equation (26), it is then apparent that a tangential force measurement error will influence both the lift and drag. Albeit, the C L is less impacted than the C D at low values of inflow angle ( ) thanks to the C t sin in the C L transfer formulae: In order to estimate the impact on the results due to tangential force uncertainty, a 2D CFD unsteady simulation using an in-house solver ISIS-CFD 50 was run.…”
Section: Tangential Force Measurement Correctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possibility (1) is restricted as the inflow turbulence in the real atmosphere is rarely low enough to prevent premature transition 10–13 …”
Section: Introductionmentioning
confidence: 99%
“…For the inflow characterization, on the other hand, it is found that integrating the spectra of pressure fluctuations obtained from the leading edge microphone in the frequency range from 100 Hz to 300 Hz represents characteristics of the inflow turbulence (11). It was seen that data captured by the microphones placed on the leading edge can be used for showing the trend for the effect of the atmospheric turbulence on boundary layer transition (3). However, microphones could only be used to show a trend.…”
mentioning
confidence: 99%